Pengaruh GDP Perkapita, FDI Dan Pertumbuhan Industri Terhadap Kualitas Lingkungan (Studi Kasus: Negara ASEAN) - Rida Fajriani; Marselina; Neli Aida; Dedy Yuliawan (CV. Multi Kreasi Media, 2023)
This study aims to analyze the effect of GDP per capita, FDI, and industrial growth on environmental quality as seen from carbon dioxide emissions in ASEAN countries. The method and analysis tool used in this research is panel data regression. The dependent variable used is carbon dioxide emissions and the independent variables include per capita GDP, FDI, and industrial growth. The best model obtained is the Fixed Effect Model. The results showed that GDP per capita and industrial growth had a positive and significant effect on the level of environmental quality in ASEAN countries, while FDI had a positive and insignificant effect on the level of environmental quality in ASEAN countries.